Transcranial magnetic stimulation for obsessive-compulsive disorder and post-traumatic stress disorder: A comprehensive systematic review and analysis of therapeutic benefits, cortical targets, and psychopathophysiological mechanisms - Vicheva, Petya; Osborne, Curtis; Krieg, Sandro; Ahmadi, Rezvan; Shotbolt, Paul (Progress in neuro-psychopharmacology & biological psychiatry, 2025)
Transcranial magnetic stimulation (TMS) is a safe non-invasive treatment technique. We systematically reviewed randomised controlled trials (RCTs) applying TMS in obsessive compulsive disorder (OCD) and post-traumatic stress disorder (PTSD) to analyse its therapeutic benefits and explore the relationship between cortical target and psychopathophysiology. We included 47 randomised controlled trials (35 for OCD) and found a 22.7 % symptom improvement for OCD and 29.4 % for PTSD. Eight cortical targets were investigated for OCD and four for PTSD, yielding similar results. Bilateral dlPFC-TMS exhibited the greatest symptom change (32.3 % for OCD, N = 4 studies; 35.7 % for PTSD, N = 1 studies), followed by right dlPFC-TMS (24.4 % for OCD, N = 8; 26.7 % for PTSD, N = 10), and left dlPFC-TMS (22.9 % for OCD, N = 6; 23.1 % for PTSD, N = 1). mPFC-TMS showed promising results, although evidence is limited (N = 2 studies each for OCD and PTSD) and findings for PTSD were conflicting. Despite clinical improvement, reviewed reports lacked a consistent and solid rationale for cortical target selection, revealing a gap in TMS research that complicates the interpretation of findings and hinders TMS development and optimisation. Future research should adopt a hypothesis-driven approach rather than relying solely on correlations from imaging studies, integrating neurobiological processes with affective, behavioural, and cognitive states, thereby doing justice to the complexity of human experience and mental illness.
Gesehen am 26.02.2025